Comparison of the effects of denosumab with either active vitamin D or native vitamin D on bone mineral density and bone turnover markers in postmenopausal osteoporosis. Issue 2 (4th March 2018) - Suzuki, Takako; Nakamura, Yukio; Tanaka, Mizue; Kamimura, Mikio; Ikegami, Shota; Uchiyama, Shigeharu; Kato, Hiroyuki
Abstract: Osteoporosis is a worldwide health concern. Although treatment with denosumab plus the active vitamin D alfacalcidol has been found to improve femoral neck (FN) and distal forearm bone mineral density (BMD), there have been no reports on the efficacy or adverse effects of denosumab plus eldecalcitol (ELD) in primary osteoporosis patients. Fifty-six treatment-naïve post-menopausal women with primary osteoporosis were recruited and divided into denosumab plus native vitamin D or denosumab plus ELD. Ultimately, 26 subjects in the native vitamin D group and 24 in the ELD group were analyzed. Lumbar and total hip BMD significantly increased in both groups. However, there was no significant difference in the percent increase of lumbar and total hip BMD between two groups. FN-BMD was significantly increased from 6 to 12 months in the ELD group compared with baseline. This study revealed that combination therapy with denosumab and ELD could improve FN-BMD more effectively than denosumab plus native vitamin D. Thus, the addition of ELD may enhance the effects of denosumab treatment for primary osteoporosis.